IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH TEXT PROJECT FOR THE SEVENTH GRADE STUDENTS OF MTS. AL-MAJIDIYAH NW SUMBAWA - Mayang Sari; IGA Widari; Solihin (STKIP Paracendekia NW Sumbawa, 2024)
This research was aimed at investigating whether “text project” if it could improve the vocabulary mastery of the students of the seventh grade of MTs. Al-Majidiyah NW and finding out how “text project” could improve their vocabulary mastery. The subjects of this research were the seventh grade students of MTs. Al-Majidiyah NW Sumbawa. There were 25 students in the class. In conducting this research, classroom action research (CAR) was applied. There were two cycles in this research which were carried out in four steps, namely planning, acting, observing, and reflecting. The data were gained through observation, documentation, and test. To analyze the data, qualitative and quantitative methods were used. Qualitative method was used to analyze the observation and documentation data. Meanwhile, the quantitative method was used to analyze the data obtained through the test. The results of the observation, documentation, and test showed that “text project” could improve the students’ vocabulary mastery. The test result in cycle I showed that the research was not successful as the classroom performance criterion that was achieved was only 72% which was still below the determined criterion (85%). After fixing and replanning some parts in cycle I, the results in cycle II, demonstrated “successful” achievement. This was because the classical performance criterion that was reached was 88%, which was already above the required criterion (85%). In other words, the improvement was 16%. Therefore, the action hypothesis of this research was accepted, that “text project does improve the students’ vocabulary mastery”.